Reference change value of global longitudinal strain in clinical practice: A test‐rest quality implementation project. Issue 12 (14th November 2022) - Tuzovic, Mirela; Tang, Xiu; Francisco, Nadia; Sell, April; Drew, Robert; Paloma, Allan; Chow, Judy; Liang, David; Heidenreich, Paul; Salerno, Michael; Schnittger, Ingela; Haddad, Francois
Abstract: Background: Reference change value (RCV) is used to assess the significance of the difference between two measurements after accounting for pre‐analytic, analytic, and within‐subject variability. The objective of the current study was to define the RCV for global longitudinal strain (GLS) using different semi‐automated software in standard clinical practice. Methods: Using a test‐retest study design, we quantified the median coefficient of variation (CV) for GLS using AutoStrain and Automated Cardiac Motion Quantification (aCMQ) by Philips. Triplane left‐ventricular ejection fraction (LVEF) was measured for comparison. Multivariable regression analysis was performed to determine factors influencing test‐retest CV including image quality and the presence of segmental wall motion abnormalities (WMA). RCV was reported using a standard formula assuming two standard deviations for repeated measurements; results were also translated into Bayesian probability. Total measurement variation was described in terms of its three different components: pre‐analytic (acquisition), analytic (measuring variation), and within‐subject (biological) variation. Result: Of the 44 individuals who were screened, 41 had adequate quality for strain quantification. The mean age of the cohort was 56.4 ± 16.8 years, 41% female, LVEF was 55.8 ± 9.8% and the median and interquartile range for LV GLS was −17.2 [−19.3 to −14.8]%. Autostrain was more time efficient (80% less analysis time) and had a lower total median CV than aCMQ (CV = 7.4% vs. 17.6%, p < .001). The total CV was higher in patients with WMA (6.4% vs. 13.2%, p  = .035). In non‐segmental disease, the CV translates to a RCV of 15% (corresponding to a probability of real change of 80%). Assuming a within‐subject variability of 4.0%, the component analysis identified that inter‐reader variability accounts for 3.7% of the CV, while acquisition variability accounts for 4.0%. Conclusion: Using test‐retest analysis and CVs, we find that an RCV of 15% for GLS represents an optimistic estimate in routine clinical practice. Based on our results, a higher RCV of 17%–21% is needed in order to provide a high probability of clinically meaningful change in GLS in all comers. The methodology presented here for determining measurement reproducibility and RCVs is easily translatable into clinical practice for any imaging parameter.